Monitoring soluble cMET and ctDNA in metastatic uveal melanoma patients to track early disease progression on immunotherapies - Machiraju, Devayani; Ziener, Christian H.; Clementi, Elena; García-Asencio, Francisco; Hüllein, Jennifer; Richter, Jasmin; Lenoir, Bénédicte; Wiecken, Melanie; Hübschmann, Daniel; Jäger, Dirk; Hassel, Jessica C. (Journal of experimental & clinical cancer research, 2025)
Background: Metastatic uveal melanoma (mUM) is a rare malignancy and is different from metastatic cutaneous melanoma (mCM) in tumor characteristics and efficacy to immunotherapies. Tumor-specific biomarkers are required for mUM patients to monitor early disease progression on immunotherapies. Methods: We investigated clinical characteristics such as liver tumor burden and routine blood tumor markers, including lactate dehydrogenase (LDH) and transaminases in patients with mUM and with liver metastasized cutaneous melanoma (LmCM), treated with immune checkpoint inhibitors (ICIs) between May 2013-February 2024. In addition, we analyzed soluble cMET (scMET) in serum samples from these patients along with a cohort of mCM patients without liver metastases (nLmCM) using ELISA. Circulating tumor DNA (ctDNA) in the plasma was analyzed using digital droplet PCR (ddPCR) in mUM patients receiving immunotherapies. scMET, ctDNA, and LDH combination was used to simultaneously monitor disease progression in ICI and tebentafusp-receiving mUM patients. Results: Sixty-nine patients with mUM and seventy-six patients with LmCM were treated with either anti-PD1 monotherapy (n = 69, 48%) or ipi + nivo combination therapy (n = 76, 52%). Irrespective of the type of melanoma and type of immunotherapy, patients with liver metastasis size greater than 8cm experienced rapid disease progression. ICI-treated mUM patients with increased LDH, aspartate aminotransferase (AST), alanine transaminase (ALT), scMET, ctDNA, and rapidly growing tumors were significantly associated with treatment resistance and shorter progression-free and overall survival (p < 0.05). scMET (AUC: 0.82) outperforms LDH (AUC: 0.77) and S100 (0.68) in predicting one-year overall survival in these patients. A validation set with LmCM and nLmCM patient samples showed that increased scMET is likely a mUM-specific feature and does not predict ICI outcomes in LmCM or nLmCM patients (p > 0.05). Moreover, monitoring ctDNA and scMET in mUM patients under ICIs or tebentafusp treatment revealed the potential for early detection of disease progression. Conclusion: Soluble cMET might serve as a tumor-specific biomarker to predict clinical outcomes in mUM patients. A combinational assessment of scMET and ctDNA in mUM patients’ blood offers a highly sensitive potential approach to monitor early disease progression under immunotherapies with ICI or tebentafusp.